Effect of low-dose aspirin use on pancreatic cancer development and morphological changes on imaging in IPMN: A long-term cohort study. Issue 7 (November 2017) - Takasaki, Yusuke; Nagata, Naoyoshi; Imbe, Koh; Hisada, Yuya; Sekine, Katsunori; Tajima, Tsuyoshi; Yanase, Mikio; Fujimoto, Kazuma; Akiyama, Junichi; Uemura, Naomi
Background: Aspirin use may reduce the incidence of pancreatic cancer (PC), but no data are available regarding its chemopreventive effects on intraductal papillary mucinous neoplasm (IPMN). We aimed to determine whether low-dose aspirin (LDA) reduces PC development and morphological changes on imaging in IPMN patients. Methods: A cohort of 448 IPMN patients periodically followed up with imaging tests was analyzed. We used one-to-two propensity score matching to adjust for differences between an LDA group ( n  = 63) and a non-LDA group ( n  = 385). Outcomes included increasing cyst diameter, increasing main pancreatic duct (MPD) diameter, mural nodule (MN) appearance and PC development. Results: After matching, 63 LDA and 126 non-LDA patients were selected. During follow-up (median, 5.5 years), no significant differences were found in increasing cyst diameter, MN appearance, or PC development. However, there were significantly fewer cases of increasing MPD diameter in the LDA group (4.8% vs. 12.7%; p  = 0.02). After adjustment for age and sex, LDA still decreased the risk of increasing MPD diameter (hazard ratio, 0.17; p  = 0.02). Conclusion: Our results do not support a chemopreventive effect of LDA on PC development. However, LDA reduces further MPD dilation in IPMN patients.